1990
DOI: 10.1128/aac.34.5.728
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oxacillin and ampicillin-sulbactam combination in experimental endocarditis caused by beta-lactamase-hyperproducing Staphylococcus aureus

Abstract: Optimal therapy of infections caused by borderline oxacillin-susceptible, 3-lactamase-hyperproducing Staphylococcus aureus has not been established. We used a rat model of aortic valve endocarditis to examine efficacies of antibiotic regimens against a borderline oxacillin-susceptible strain as compared with a fully susceptible S. aureus strain. Animals were treated with oxacillin alone or in combination with sulbactam or with ampicillin-sulbactam combinations at two dose levels. Infections caused by the borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
2
26
0
1
Order By: Relevance
“…We speculated that these results may have been influenced to a large degree by the striking ability of sulbactam to induce 1-lactamase production in BOSSA strains and to a much lower extent in OSSA strains, a phenomenon which we demonstrated in vitro (12). This hypothesis was supported by the observation that addition of sulbactam to oxacillin tended to antagonize the in vivo activity of the latter against both strains, although the differences observed did not reach statistical significance.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…We speculated that these results may have been influenced to a large degree by the striking ability of sulbactam to induce 1-lactamase production in BOSSA strains and to a much lower extent in OSSA strains, a phenomenon which we demonstrated in vitro (12). This hypothesis was supported by the observation that addition of sulbactam to oxacillin tended to antagonize the in vivo activity of the latter against both strains, although the differences observed did not reach statistical significance.…”
supporting
confidence: 70%
“…Inhibition of such isolates required methicillin and oxacillin concentrations of 4 and 2 ,ug/ml, respectively, but full susceptibility could be restored by combination of an antistaphylococcal penicillin with a ,B-lactamase inhibitor such as clavulanic acid or sulbactam. In a previous study, we examined the in vivo activities of ampicillin-sulbactam and oxacillin in a rat model of experimental endocarditis caused by such a borderline oxacillin-susceptible S. aureus (BOSSA) strain in comparison with endocarditis caused by a fully oxacillin-susceptible S. aureus (OSSA) strain (12). We found that oxacillin was equally effective against BOSSA and OSSA strains, reducing bacterial densities in cardiac vegetations from more than 1010 CFU/g to between io4 and io CFU/g.…”
mentioning
confidence: 99%
“…BSSA strains generally belong to phage group 94/96, possess a unique 17.2-kb plasmid, and produce generous amounts of the type A variant of staphylococcal P-lactamase (4,28). Infections by these strains generally are responsive to therapy with the penicillinase-resistant penicillins (25,37). BSSA strains exhibit very rapid degradation of ampicillin ( …”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed by some authors that there is no apparent reason for BORSA strains to be considered resistant to all other ␤-lactams (5,18,22). Therefore, infections caused by these strains can probably be safely and effectively treated with ␤-lactam antibiotics, including cloxacillin, or with the use of a ␤-lactam-␤-lactamase inhibitor combination (16,26,27). However, other authors have demonstrated that oxacillin has not been effective against BORSA strains (8,23).…”
mentioning
confidence: 99%